Analysis of coral cover using the Underwater Photo Transect (UPT) method on Tidung Island, the Thousand Islands, Indonesia - Effendi, Muhammad Ardiansyah; Maisaroh, Dian Sari; Munir, Misbakhul; Widodo, Mikael Prastowo Sesotyo (Journal of Marine Resources and Coastal Management, 2026)
Coral reef ecosystems are important marine ecosystems that provide ecological, economic, and social benefits, but their condition is increasingly threatened by anthropogenic activities and environmental pressures. Tidung Island is a marine tourism destination with relatively high human activity, which may affect the condition of its coral reef ecosystem. This study aimed to assess the condition of coral reef cover and identify the environmental conditions associated with differences in coral reef conditions around Tidung Island, Thousand Islands, DKI Jakarta. The study was conducted from May, 14–18 2026 using a quantitative descriptive approach. Coral cover data were collected using the Underwater Photo Transect (UPT) method at four observation stations, with photographs analyzed using Coral Point Count with Excel extensions (CPCe). Hydro-oceanographic parameters, including temperature, salinity, water clarity, and pH, were also measured at each station. The results showed considerable variation in live coral cover among stations. Station 3 had the highest coral cover at 55.3% and was categorized as good, while Stations 1 and 2 had coral cover of 31.6% and 31.4%, respectively, and were categorized as moderate. Station 4 had the lowest coral cover at 3.3%, indicating a degraded condition. The overall average coral cover was 30.5%, indicating that the general condition of coral reefs ranged from moderate to degraded. Hydro-oceanographic parameters generally fall within a range that supports coral reef development, with temperatures of 30–31°C, salinity of 30–31‰, water clarity of 5–8 m, and a pH of 7. Therefore, anthropogenic pressures and physical disturbances—particularly tourism, boat moorings, fishing, and maritime transportation—are suspected to be factors contributing to coral reef degradation, rather than the measured hydro-oceanographic conditions. These findings highlight the need for better management, reduction of anthropogenic pressures, and more intensive conservation efforts to support the recovery and sustainability of coral reefs around Tidung Island.